Redescription of Crassomicrodus fulvescens (Cresson) (Hymenoptera: Braconidae: Agathidinae), with new distributional data and revised taxonomic status - Figueroa, José Isaac; Sharkey, Michael J.; Nápoles, Jesús Romero; López-Martínez, Victor; García, José Antonio Sánchez; Martínez, Ana Mabel; Pineda, Samuel (Zootaxa, 2008)
A detailed description of the adult of Crassomicrodus fulvescens (Cresson) is provided along with illustrations. New distributional data in the USA and Mexico are presented, and the first records from Canada are reported. Microdus medius Cresson is found to be a junior subjective synonym of M. fulvescens. Autographa californica (Speyer) is reported as a possible host for C. fulvescens based exclusively on label data.